Extensive Longitudinal Transverse Myelitis Temporally Related to the Use of AZD1222, AstraZeneca COVID-19 Vaccine: Cerebrospinal Fluid Analysis and Recent Data Review - Paulo Diniz da Gama; Tiago Gomes de Alcantara; Rafaela Ramos Smaniotto; Penélope de Lima Petuco; Wammer Alves de Almeida; Rodrigo Assad Diiniz da Gama; Yara Dadalti Fragoso (Case Reports in Neurological Medicine)
While mass immunization against coronavirus disease 2019 (COVID-19) rolls out around the globe, safety concerns and adverse events that need prompt evaluation are also emerging. Neurological complications such as transverse myelitis raise concerns as cases were observed in clinical trials. Cerebrospinal fluid analysis is routine in these cases and the characteristics of the abnormalities found are of great help not only in establishing the diagnosis but also in understanding this rare condition. We present a case of extensive longitudinal transverse myelitis after vaccination with AZD1222, AstraZeneca COVID-19 vaccine, which was the first case reported in Brazil. The abnormalities found in the study of the cerebrospinal fluid in our case are reported and discussed using data from recent publications.